Achondroplasia: a case report and the review of the basics - Agrawal, Sujan Narayan (International Surgery Journal, 2020)
The achondroplasia is a variant of short-limbed dwarfism. The word achondroplasia literally means without cartilage formation. However, in achondroplasia the problem is not in formation of cartilage but, in its conversion to bone (i.e. ossification). This deficient ossification is particularly seen in the long bones of arm and leg. The characteristic external appearance of people born with achondroplasia is short stature. The average height of an adult male with achondroplasia is 131 centimetres (4 feet, 4 inches), and the average height for adult females is 124 centimetres (4 feet, 1 inch). The trunk is of average size but the leg and upper arm is of short length. It is because the femur and humerus are relatively shorter in length. The range of movement at elbow is limited. The head is enlarged called macrocephaly and is with a prominent forehead. People with Achondroplasia are generally of normal intelligence. They have bowed legs and abnormal curvature of spine giving rise to lordosis or kyphosis. They may develop spinal stenosis, which is associated with pain, tingling and weakness in leg. This may cause difficulty in walking. The other health problems associated with Achondroplasia are episodes of apnoea, obesity and recurrent ear infection. The purpose of this study is to evaluate the cardinal phenotypic features in patient of Achondroplasia. It is also to assess the body physique, anthropometric measurements and to study the typical radiological signs in such patients as the main tool of diagnosis.